Community Development Based on Community Media: Case Study of Angkringan Community in Yogyakarta - Syatori, A (Universitas Negeri Semarang, 2023)
This study seeks to examine and analyze the process and strategy of community development based on community media namely Angkringan in Bantul Yogyakarta, based on the conceptual scheme (Habitus) (Capital) + Field = Practice established by Pierre Bourdieu. Within this scheme, the community development means the dynamic of social practice of social agents in which case the combination of habitus, objective structure and a big set of other strategies make and bind such dynamic. This study employs a qualitative approach for which the data collection method combines some in-depth interviews, document studies, and literature studies. This investigation reveals that Angkringan develops its community by utilizing various types of media ranging from print media (bulletin), audio media (radio), audio visual media (Video and Community TV), to internet technology. Through the bulletin, Angkringan has been presenting various ideas and discourses on the necessity of considering various issues that hover the community. Angkringan also opens a kind of public space for community members to express complaints, making suggestions, criticizing and even litigating for anything that is taken as ‘problematic’. Radio Angkringan offers an opportunity for some interactive dialogues between citizens and village government in the community. Moreover, internet technology is the most recent and spectacular phase as a series of social practices launched by Angkringan in order to develop its community. Through internet media, Angkringan seeks to develop community in a wider domain by developing community networks throughout the archipelago and even the world.